SIMULATION OF EFFICIENCY IN AVAILABILITY FOR DIFFERENT SUGARCANE (Saccharum spp.) TRANSPORT EQUIPMENT - Santos,Neisvaldo B. dos (2022)
ABSTRACT Brazil is the world’s largest sugarcane producer destined for mills producing alcohol, sugar, and electricity cogeneration. Sugarcane transport to the mills is carried out by trucks with trailers and tractors with semi-trailers, which transport the raw material harvested in the field to the mill. The modal road system of sugarcane transport uses this equipment to meet the continuous demand of the harveste draw material, with punctuality in the transport execution and generating a minimum cost. This study aimed to analyze the influence of availability efficiency on the operational and economic performance of different sugarcane transport equipment. A computational model called TransporteCana was developed in a spreadsheet due to the difficulty in meeting the objective under field conditions. The model was checked for possible routine errors, validated, and used in the analysis of variables and generation of results. The results showed that increasing availability efficiency reduces the operational cost of producing the equipment. Large managerial investments for the means of execution are required for high availability efficiencies.